«Una disciplina misteriosa e inquietante»: Considerazioni sulla meccanica quantistica e il suo rapporto con la filosofia. - Bongiovanni, Secondo (Rassegna di teologia, 2026)
The study offers a nonspecialist overview of some decisive turning points in the quantum revolution of the Twentieth century, aiming to avoid certain simplifications that appear at times in popular science. Without claiming to be exhaustive, the work seeks to bring to light questions and insights able to engaging not only philosophy but also theology. The perspective opened by quantum physics may indeed help "broaden the horizons of rationality," as Benedict XVI hoped.